FAMILIAL BENIGN RECURRENT VERTIGO AND ITS RELATIONSHIP TO MIGRAINE: CLINICAL DESCRIPTIONS OF EIGHT FAMILIES. (1st January 2005) - Wangu, Z.; Trees, N.; Jen, J.; Baloh, R. W.
Abstract : Objective: Migraine is a disease of chronic headaches that is associated with a spectrum of signs and symptoms often including vertigo, or an illusory sensation of spinning. Familial benign recurrent vertigo (BRV) is a genetic condition displaying autosomal dominant inheritance. Although migraine may accompany BRV, BRV typically occurs independently of migraine. In this study, it was hypothesized that BRV is a migraine-associated disorder. Method: Thirty-two BRV patients from eight different families were assessed for symptoms via telephone interviews using standardized questionnaires. The patients were then compared in terms of specific symptoms such as onset age, duration, and frequency of vertigo attacks as well as the relationship of vertigo to migraine. Results: The majority of patients experienced a frequency of vertigo attacks of once per month to once per year with a typical duration of minutes to hours. The average age of vertigo onset ranged from the late teens to late thirties, with a majority in the mid to late twenties. A significant percentage of all BRV patients experienced migraine as well, including headache and visual aura. Furthermore, imbalance, nausea, and ear or head pressure/stuffiness typically accompanied vertigo attacks, and hearing loss and tinnitus were the most common associated neurological conditions in this group of patients. Conclusions: BRV is strongly associated with migraine in these families and patients experienced similar symptoms with their dizziness. Each family, however, varied in specific phenotypes suggesting multiple genetic syndromes.